THE DIGITAL LITERACY PARADOX: GEN Z, INFORMATION OVERCONFIDENCE, AND THE EROSION OF TRUST IN SCIENTIFIC AUTHORITY: - Fikri Reza; Metha Madonna (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Generation Z is widely perceived as digitally competent, yet extensive access to information does not necessarily translate into critical evaluation skills. This systematic literature review examines the digital literacy paradox—the gap between perceived and actual information literacy—and its implications for trust in scientific authority. Following the PRISMA 2020 guidelines, literature published between 2015 and 2026 was identified from six databases. Of 1,226 records, 20 studies met the inclusion criteria for thematic synthesis. The review identifies four findings: assumptions of innate digital competence lack consistent empirical support; perceived literacy often exceeds actual competence, reflecting the Dunning–Kruger effect and the illusion of knowledge from online search; platform-driven information practices encourage reliance on non-authoritative sources; and interventions based on critical digital literacy, lateral reading, and psychological inoculation remain underdeveloped in Indonesia. The review concludes that declining trust in science is fundamentally a metacognitive and epistemic challenge requiring educational approaches that foster intellectual humility.